Biomechanics for Orthodontic Intrusion of Severely Extruded Maxillary Molars for Functional Prosthetic Rehabilitation - Ivan Pedro Taffarel; Thiago Martins Meira; Lara Karolina Guimarães; Oscar Mario Antelo; Orlando Motohiro Tanaka (Case Reports in Dentistry)
The objective of this clinical case is thus to present a Class II, division 1, subdivision malocclusion with a severely extruded maxillary left hemiarch, which, due to the loss of mandibular teeth, makes prosthetic rehabilitation of the edentulous spaces impossible. A significant intrusion was performed with mini-implants followed by miniplates associated with fixed appliance and elastomeric chains. The results of this process showed that the biological responses of the teeth and the surrounding bony structure to the intrusion were demonstrated to be normal and acceptable. A clinically significant intrusion of the left maxillary molars, along with the recovery of the interocclusal space and the prosthetic rehabilitation, was obtained with a fixed orthodontic appliance that was associated to the biomechanics with TADs. It also allowed the obtaining of Class I canine relationship, demonstrated periodontal health and favored the prosthetic rehabilitation with good occlusion, aesthetics, and satisfactory function.